Diagnosis of Primary Langerhans Cell Histiocytosis of the Vulva in a Postmenopausal Woman - Sefa Kurt; Mehmet Tunc Canda; Aycan Kopuz; Dudu Solakoglu Kahraman; Abdullah Tasyurt (Case Reports in Obstetrics and Gynecology)
Langerhans cell histiocytosis (LCH) is a very rare disease of female genital tract, most commonly seen in vulva and unusual in postmenopausal period. Herein, we report the 8th case of pure vulvar LCH in a postmenopausal woman. We pay attention to the differential diagnosis in postmenopausal state, features of pathologic diagnosis, and treatment options.